(untitled) (Research, Society and Development, 2019)
This article aims to reflect on teacher-mediated learning according to Vygotsky’s approach. Through a qualitative study of a theoretical nature, we sought to analyze the concepts of mediation and Zone of Proximal Development (ZPD), to understand how a mediating teacher can enable effective learning in the students. The mediating teacher appears as a figure of paramount importance for the development of the student and his / her learning, leading him to interact with the environment in the search for a contextual knowledge elaborated from social exchanges. Through this study, it was possible to highlight the importance of the role of the teacher as mediator of the learning processes, therefore, as a fundamental figure to develop it in the teaching processes.